Assessing the Effectiveness of CCME-WQI, NSF-WQI, OWQI, and Smith Index Water Quality Indices in Karst Areas - Almira Rahma Hinanto; Margaretha Widyastuti; Eko Haryono (School of Postgraduate Studies, Diponegoro Univer, 2024)
Water quality assessment employs various methods, including water quality indices (WQI). This study compares several WQI methods to evaluate Sumurup River and Seropan Underground River in Gunungkidul Regency. The study aims to analyze the effectiveness of CCME-WQI, NSF-WQI, OWQI, and Smith Index methods. Parameter selection was conducted using Principal Component Analysis, and the NSF-WQI method was found to best represent water quality in the study area. OWQI produced consistently poor results due to an overly idealized formula, while CCME-WQI's sensitivity to parameter number reduced its effectiveness. The Smith Index, based on New Zealand standards, yielded the lowest quality results, regardless of parameter modifications. Thus, NSF-WQI is recommended for assessing water quality in karst areas like Sumurup and Seropan Underground Rivers. This research underscores the importance of selecting appropriate WQI methods tailored to specific environmental conditions to support effective water resource management and conservation efforts.